Color image encryption based on interference and virtual optics - Quan, Chenggen (2010)
We propose two approaches to encrypt color images based on interference and virtual optics. In the first method, a color image is first decomposed into three independent channels, i.e., red, green and blue.Each channel of the input image is encrypted into two random phase-only masks based on interference.In the second method, a color image is first converted into an image matrix and a color map, and only the image matrix is encrypted into random-phase masks based on interference. After the phase masks are retrieved, a concept based on virtual optics is further applied to enhance the security level. Numerical simulations are demonstrated to show the feasibility and effectiveness of the proposed methods.